Card9 controls Dectin-1-induced T-cell cytotoxicity and tumor growth in mice - Haas, Tobias; Heidegger, Simon; Wintges, Alexander; Bscheider, Michael; Bek, Sarah; Fischer, Julius C.; Eisenkolb, Gabriel; Schmickl, Martina; Spoerl, Silvia; Peschel, Christian; Poeck, Hendrik; Ruland, Juergen (European Journal of Immunology, 2017)
Activation of the C-type lectin receptor Dectin-1 by β-glucans triggers multiple signals within DCs that result in activation of innate immunity. While these mechanisms can potently prime CD8+ cytotoxic T-cell (CTL) responses without additional adjuvants, the Dectin-1 effector pathways that control CTL induction remain unclear. Here we demonstrate that Dectin-1-induced CTL cross-priming in mice does not require inflammasome activation but strictly depends on the adapter protein Card9 in vitro. In vivo, Dectin-1-mediated Card9 activation after vaccination drives both expansion and activation of Ag-specific CTLs, resulting in long-lasting CTL responses that are sufficient to protect mice from tumor challenge. This Dectin-1-induced antitumor immune response was independent of NK cell function and completely abrogated in Card9-deficient mice. Thus, our results demonstrate that Dectin-1-triggered Card9 signaling but not inflammasome activation can potently cross-prime Ag-specific CTLs, suggesting that this pathway would be a candidate for immunotherapy and vaccine development.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Card9; CD8; Cross-priming; Dectin-1; Tumor immunity